Estado de emergência na saúde pública e intervenção estatal na vida privada: para além da invasão e da revolta - Paula, Rodrigo Francisco de (2016)
This thesis makes a critical analysis on legitimacy of actions from Government in the emergency state of public health, when these actions results in state interference in private life. Bases are presented considering legal doctrines to allow them to be determined by the Executive forced restricted measures of the individual freedom in order to protect and defend public health. This perspective is criticized for not considering related risks detaching the potentiality of a state of permanent exception, because the epidemiological speech created around prevention and control is generated by typical speech unities in the law speech with the power over the state of exception concerning the need of understanding justification and application of the constitutional rules in Brazil, according to peculiarities of Brazilian constitutionalism being most part of the population living without any access to the most basic citizen rights. That is why it is an attempt to (re)tell the constitutional history of Brazil presenting the bases for a fair memory politics including the Vaccine Rebellion (1904) in this history taking into consideration the rebels actions from a plausible exercise of rights according to the Constitution of 1891. Between past and present of Brazilian constitutionalism, it proposes the identification of a regulatory policy for the Government actions in the emergency state of public health criticizing the adoption of measures that restrain individual freedom conceived only in the field of epidemiological speech. Discussion about its limits and possibilities, including the risk of establishing a state of exception in the name of public health for beyond the constitutional possible ways (state of defense and state of siege), and finally supporting the dignity of rebellion as a political act facing the absurd of hygienist policy.